2001
DOI: 10.1152/jappl.2001.91.3.1035
|View full text |Cite
|
Sign up to set email alerts
|

On the functional consequences of bronchial basement membrane thickening

Abstract: Reticular basement membrane (RBM) thickness and airway responses to inhaled methacholine (MCh) were studied in perennial allergic asthma (n = 11), perennial allergic rhinitis (n = 8), seasonal allergic rhinitis (n = 5), and chronic obstructive pulmonary disease (COPD, n = 9). RBM was significantly thicker in asthma (10.1 +/- 3.7 microm) and perennial rhinitis (11.2 +/- 4.2 microm) than in seasonal rhinitis (4.7 +/- 0.7 microm) and COPD (5.2 +/- 0.7 microm). The dose (geometric mean) of MCh causing a 20% decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 27 publications
3
97
0
8
Order By: Relevance
“…Indeed, it has been proposed that RBM thickening may be protective rather than deleterious [5,6]. Although our failure to show a relationship between RBM thickness and impaired lung function may be a power issue, it is also compatible with the view that increased RBM thickness does not have adverse physiological effects [6].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, it has been proposed that RBM thickening may be protective rather than deleterious [5,6]. Although our failure to show a relationship between RBM thickness and impaired lung function may be a power issue, it is also compatible with the view that increased RBM thickness does not have adverse physiological effects [6].…”
Section: Discussionsupporting
confidence: 84%
“…However, the physiological consequences of pathological changes in the asthmatic airways are poorly understood. While some adult studies show that increased reticular basement membrane (RBM) thickness is associated with airway obstruction [4], others show that RBM thickening is protective against bronchoconstriction [5,6]. Contemporaneous studies of pathology and function in preschool children with recurrent wheeze are lacking, due to ethical concerns over performing endobronchial biopsies and preschool lung function testing being limited to specialist centres.…”
mentioning
confidence: 99%
“…They revealed that the thickness of basement membrane in the patients with mild perennial asthma and perennial allergic rhinitis was significantly higher than in the patients with seasonal rhinitis and COPD. In addition, thickness of basement membrane in the patients with asthma showed a positive relationship with provocative dose of methacholine in airway hyperresponsiveness (Milanese et al 2001). These results suggest that reduction of elasticity in airway is associated with progress of thickness of basement membrane.…”
Section: Thickening Of Epithelial Basement Membrane and Subepithelialmentioning
confidence: 63%
“…Ward et al (2001) showed a negative relationship between the distensibility of airway and thickness of basement membrane. Furthermore, Milanese et al (2001) measured thickness of epithelial basement membrane of bronchial tissues obtained by transbronchial biopsy from patients with mild perennial asthma, perennial allergic rhinitis, seasonal rhinitis and chronic obstructive pulmonary disease (COPD). They revealed that the thickness of basement membrane in the patients with mild perennial asthma and perennial allergic rhinitis was significantly higher than in the patients with seasonal rhinitis and COPD.…”
Section: Thickening Of Epithelial Basement Membrane and Subepithelialmentioning
confidence: 99%
“…Airway remodelling is a well-documented phenomenon associated with asthma development. Thickening of some airway wall components seen in asthmatic airways may contribute to excessive airway narrowing [146]; thickening of other components may have a protective effect against excessive narrowing [147][148][149][150][151]. Many of these predictions were based on computer simulations of geometrical changes in airway components and, therefore, were limited by the assumptions associated with the simulation.…”
Section: Removal Of Smooth Muscle From Asthmatic Airwaysmentioning
confidence: 99%